Excitation-contraction coupling and mechano-sensitivity in denervated skeletal muscles - Fabio Francini; Roberta Squecco (PAGEPress Publications, 2010)
Skeletal muscle atrophy can be defined as a wasting or decrease in muscle mass and muscle force generation owing lack of use, ageing, injury or disease. Thus, the etiology of atrophy can be different. Atrophy in denervated muscle is a consequence of two factors: 1) the complete lack of motoneuron activity inducing the deficiency of neurotransmitter release and 2) the muscles disuse. The balance of the muscular functions depends on extra- and intra-muscular signals. In the balance are involved the excitation-contraction coupling (ECC), local growth factors, Ca2+-dependent and independent intracellular signals, mechano-sensitivity and mechano-transduction that activate Ca2+-dependent signaling proteins and cytoskeleton- nucleus pathways to the nucleus, that regulate the gene expression. Moreover, retrograde signal from intracellular compartments and cytoskeleton to the sarcolemma are additional factors that regulate the muscle function. Proteolytic systems that operate in atrophic muscles progressively reduce the muscle protein content and so the sarcolemma, ECC and the force generation. In this review we will focus on the more relevant changes of the sarcolemma, excitation-contraction coupling, ECC and mechano-transduction evaluated by electrophysiological methods and observed from early- to long-term denervated skeletal muscles. This review put in particular evidence that long-term denervated muscle maintain a sub-population of fibers with ECC and contractile machinery able to be activated, albeit in lesser amounts, by electrical and mechanical stimulation. Accordingly, this provides a potential molecular explanation of the muscle recovery that occurs in response to rehabilitation strategy as transcutaneous electrical stimulation and passive stretching of denervated muscles, which wre developed as a result of empirical clinical observations.